2004
DOI: 10.1073/pnas.0406024101
|View full text |Cite
|
Sign up to set email alerts
|

The topological relationship between the large-scale attributes and local interaction patterns of complex networks

Abstract: Recent evidence indicates that the abundance of recurring elementary interaction patterns in complex networks, often called subgraphs or motifs, carry significant information about their function and overall organization. Yet, the underlying reasons for the variable quantity of different subgraph types, their propensity to form clusters, and their relationship with the networks' global organization remain poorly understood. Here we show that a network's large-scale topological organization and its local subgra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
236
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(245 citation statements)
references
References 35 publications
6
236
1
2
Order By: Relevance
“…Several studies have further investigated the connection between network motif enrichment and aggregation, from a topological as well as from an evolutionary perspective. In hierarchical scale-free random networks the enrichment and aggregation of a certain class of subgraphs are intimately related to each other and to the global topological network parameters 11 . Furthermore these subgraphs tend to aggregate around network hubs 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have further investigated the connection between network motif enrichment and aggregation, from a topological as well as from an evolutionary perspective. In hierarchical scale-free random networks the enrichment and aggregation of a certain class of subgraphs are intimately related to each other and to the global topological network parameters 11 . Furthermore these subgraphs tend to aggregate around network hubs 11 .…”
Section: Introductionmentioning
confidence: 99%
“…In hierarchical scale-free random networks the enrichment and aggregation of a certain class of subgraphs are intimately related to each other and to the global topological network parameters 11 . Furthermore these subgraphs tend to aggregate around network hubs 11 . A comparative phylogenetic analysis of genes within motifs has shown that they are not subject to any evolutionary pressure to preserve the motif pattern 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been a growing industry in the application of complex network theory to carry out time series analysis [23,24]. The time series firstly is transformed into networks and then analyzed with various complex network tools [25][26][27][28]. Shirazi et al [29] demonstrated that the time series can be reconstructed with high precision by means of a simple random walk on their corresponding networks.…”
Section: Introductionmentioning
confidence: 99%
“…This approach have proven to be useful to identify non trivial properties of the structure of networks in very different contexts. We can cite for instance computer networks (like the Internet, peer-to-peer systems, the web) [1], [2], biological networks (protein-protein interaction networks, metabolic processes) [3], [4], social networks (friendship networks, co-publication networks) [3], [5], legal networks [6], linguistics [7], economy [8], etc.…”
Section: Introductionmentioning
confidence: 99%